Helicobacter pylori non-cytotoxic genotype enhances mucosal gastrin and mast cell tryptase. Issue 3 (1st March 1999) - Basso, D; Navaglia, F; Brigato, L; Di Mario, F; Rugge, M; Plebani, M
Abstract : AIMS: To determine the association, if any, between H pylori genotype and the gastric mucosal variations in the levels of gastrin, somatostatin, tryptase, and histamine. METHODS: 49 patients affected by duodenal ulcer and 48 by non-ulcer dyspepsia were studied. To identify the H pylori genotype, the presence of the cagA gene and vacA alleles m1, m2, s1, and s2 were analysed by polymerase chain reaction. Gastrin, somatostatin, tryptase, and histamine were measured in antral mucosal biopsies. RESULTS: 57 patients were infected with H pylori (30 with duodenal ulcer and 27 with non-ulcer dyspepsia). Gastrin and tryptase were increased in patients with H pylori infection, although the variations were statistically significant only for gastrin; somatostatin and histamine were not influenced by H pylori infection. In patients with non-ulcer dyspepsia the absence of the cagA gene and the presence of vacA alleles s2 and m2 were associated with higher values of tryptase and to a lesser extent of gastrin. These associations were not found in patients with duodenal ulcer. CONCLUSIONS: The cagA negative s2m2 strain of H pylori may be less dangerous for the gastric mucosa than other H pylori strains since it enhances tryptase production by gastric mucosal mast cells; this enzyme is thought to stimulate tissue turnover and favour wound healing.